Laboratory investigation and efficiency of deicing materials used in road maintenance - Ružinskas, Andrius; Bulevičius, Matas; Sivilevičius, Henrikas (Transport, 2016)
Snow and ice cause considerable traffic problems on roads and streets in the winter period. Timely and effective removal of these problems can prevent major car accidents. This paper presents an analysis of the efficiency of Deicing Materials (DMs) used by the Lithuanian road maintenance agencies. Five different DMs were studied by performing ice melting tests in the laboratory. DMs were evenly spread on the formed ice samples taking the same amount of grains of uniform size. The ice mass dissolved by each DM was determined at different durations of melting action, ranging from 4 to 120 min, and at different ambient temperatures, ranging from –20 to –3 °C. The obtained results of each DM were analysed, and all the tested materials were compared under different temperature conditions. In addition, the deicing speed of each DM was calculated, and the DM was categorized according to the efficiency performance. A comparison of tested DM efficiencies was carried out, and the price of one percent of melted ice was determined.